1999
DOI: 10.1007/s000270050050
|View full text |Cite
|
Sign up to set email alerts
|

Soluble iron sulfide species in natural waters: Reappraisal of their stoichiometry and stability constants

Abstract: A wide range of stoichiometries has been previously proposed for soluble iron sulfide species and there is no general agreement on their importance in natural waters. The solubility of Fe(II) in 0.1 M NaClO 4 equilibrated at 20 ± 0.1°C with various partial pressures of H 2 S (0.1, 0.001, 0.0001, 0.00001 MPa) was measured in the pH range 3.1-7.9. Equilibrium was established within 1 -6 h when amorphous FeS was the solid phase. The results could all be fitted using values for the solubility product constant (I =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
91
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 27 publications
(41 reference statements)
5
91
1
Order By: Relevance
“…where ␤ 1 ϭ 10 ϩ2.05Ϯ0.5 (Luther et al, 1996), ␤ 2 ϭ 10 Ϫ3.43Ϯ0.1 (Davison et al, 1999). The way reactions 4, 5, and 1 are written simplifies further derivations; no assumptions about the actual reactive species or reaction mechanisms are made.…”
Section: Solubilitymentioning
confidence: 99%
See 3 more Smart Citations
“…where ␤ 1 ϭ 10 ϩ2.05Ϯ0.5 (Luther et al, 1996), ␤ 2 ϭ 10 Ϫ3.43Ϯ0.1 (Davison et al, 1999). The way reactions 4, 5, and 1 are written simplifies further derivations; no assumptions about the actual reactive species or reaction mechanisms are made.…”
Section: Solubilitymentioning
confidence: 99%
“…Aqueous iron-sulfide complexation plays an important role in this pH range (Rickard, 1989;Davison, 1991;Luther, 1991;Luther and Ferdelman, 1993;Zhang and Millero, 1994;Rickard, 1995;Luther et al, 1996;Davison et al, 1999). The two most simple complexation reactions reported are…”
Section: Solubilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Iron is also able to form Fe-sulfide complexes and clusters in the aqueous phase. Davison et al (1999) demonstrated that, in a solution saturated with respect to FeS(s), the formation of aqueous Fe(HS)2 and Fen(HS)2n (n ≥2) complexes may explain the solubility. Using an alternative approach, Rickard (2006) suggested that the dissolution of FeS(s) involves the formation of aqueous FeS nano-clusters (i.e.…”
Section: Regulation Of Metals Bio-uptakementioning
confidence: 99%